2012
DOI: 10.2174/1874325001206010419
|View full text |Cite
|
Sign up to set email alerts
|

Multifragmentary Tibial Pilon Fractures: Midterm Results After Osteosynthesis with External Fixation and Multiple Lag Screws

Abstract: Osteosynthesis of intraarticular tibial pilon fractures is preferably achieved using locking plates via a minimally invasive technique. If combined with severe soft tissue damage there is a high risk of wound-healing deficits after plate osteosynthesis. Thus our aim was to find an alternative method of treatment for those cases with combined soft tissue injuries.We report on five cases with comminuted fractures of the joint surface combined with critical soft tissue condition that were treated with lag screws … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…These are overall satisfactory results. Ketz et al found an average of 76.4 and 85.2 points in the AOFAS score in their groups of type C2 and C3 fractures, respectively, after plate osteosynthesis using different approaches; Kiene et al described a mean AOFAS score of 81 points after a combination of external fixation and lag screws [19,20]. Our study has some limitations: It was a retrospective single-centre study, and different fracture patterns were treated using different stabilisation techniques, including angular stable plates and external fixators as required.…”
Section: Discussionmentioning
confidence: 99%
“…These are overall satisfactory results. Ketz et al found an average of 76.4 and 85.2 points in the AOFAS score in their groups of type C2 and C3 fractures, respectively, after plate osteosynthesis using different approaches; Kiene et al described a mean AOFAS score of 81 points after a combination of external fixation and lag screws [19,20]. Our study has some limitations: It was a retrospective single-centre study, and different fracture patterns were treated using different stabilisation techniques, including angular stable plates and external fixators as required.…”
Section: Discussionmentioning
confidence: 99%
“…Where is caused by trauma of high kinetic energy, where the metaphyseal-epiphyseal fragments impacted are solid metaphyseal. He is also known as axial compression and usually caused by trauma falling from great heights or traffic accident [5,6]. It is usually associated with severe soft tissue injuries associated with foot and ankle edema great causing bleeding from blisters, predisposing to infection [12].…”
Section: Discussionmentioning
confidence: 99%
“…The fall caused a physeal fracture of the fibula and left tibia with intra-articular involvement, (fractures of the tibial pilon, type III) [5], which is a relatively uncommon fracture therefore affects only 1% of the fracture of the lower limbs [6,7]. Following the classic protocol of this type of fracture, surgery was indicated immediately with the need to metallic syntheses.…”
Section: Case Studymentioning
confidence: 99%
“…Davidovitch et al describe that both ORIF and EF appear to be comparable for treatment of TPF fractures with regard to final range of ankle motion, development of arthritis and hind foot scores [8]. Kiene et al propose combined treatment using lag screws with external fixation as a practical treatment option for those fractures for which lag screws combined with a locking plate are not feasible or when there is a high risk of wound-healing deficits due to severe soft tissue damage [9]. Wang et al show that in the treatment of closed tibial plafond fractures; both two-staged ORIF and LIFEF offer similar results [10].…”
Section: Advantages Of Minimally Invasive Osteosynthesis Of Pilon Framentioning
confidence: 99%